2017
DOI: 10.3389/fimmu.2017.01883
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoglobulin G1 Allotype Influences Antibody Subclass Distribution in Response to HIV gp140 Vaccination

Abstract: Antibody subclasses exhibit extensive polymorphisms (allotypes) that could potentially impact the quality of HIV-vaccine induced B cell responses. Allotypes of immunoglobulin (Ig) G1, the most abundant serum antibody, have been shown to display altered functional properties in regard to serum half-life, Fc-receptor binding and FcRn-mediated mucosal transcytosis. To investigate the potential link between allotypic IgG1-variants and vaccine-generated humoral responses in a cohort of 14 HIV vaccine recipients, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Several studies have examined the impact of serologically defined IgG allotypes on function, disease susceptibility and response to HIV vaccination, highlighting the relevance of genetic variation in the constant region [21, 69]. However, IgG allotypes encompass multiple alleles and do not fully describe allelic variation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the impact of serologically defined IgG allotypes on function, disease susceptibility and response to HIV vaccination, highlighting the relevance of genetic variation in the constant region [21, 69]. However, IgG allotypes encompass multiple alleles and do not fully describe allelic variation [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IgG polymorphisms may also be associated with altered class switching efficiency, through variations within the noncoding switch regions, which would subsequently affect serum concentrations [93,95,96]. In a recent study, Shattock and colleagues showed that IgG1 allotypic variants were associated with the subclass distribution (IgG1/IgG2) of an HIV-specific antibody response, illustrating the association of IgG polymorphisms with the tendency for particular IgG subclass switching [97].…”
Section: Igg Allotypesmentioning
confidence: 99%
“…An overview of FcγR biology has been recently summarized and so our focus for this review will be to evaluate the effect of genetic variation in the human Fcγ receptors and their role specifically in HIV-1 disease pathogenesis (6). Although there is evidence that the neonatal Fc receptor (FcRn), an MHC class I-related molecule expressed on many cells, functions in HIV-1 vaccination and infection (7, 8), no significant genetic variation has been identified for this locus, and we have not included it in this review.…”
Section: Introductionmentioning
confidence: 99%